Convergence of Banking Law and Commodity Futures Law in the Practice of Bullion Banking - Diana R.W. Napitupulu (Jurnal Ilmu Hukum, 2026)
This research examines the evolving legal convergence between banking law and commodity futures law in the governance of bullion banking activities. Bullion banking represents a hybrid financial practice in which gold functions simultaneously as a physical commodity, a financial asset, and an underlying instrument in derivatives markets. Through various mechanisms such as unallocated gold accounts, gold lending and leasing, swaps, and over-the-counter derivatives transactions, bullion banks perform activities that both resemble and combine the functions of deposit-taking institutions and commodity market intermediaries. This dual characteristic challenges traditional regulatory classifications and creates tensions between prudential supervision in the banking sector and market conduct regulation in the derivatives sector. Using a normative juridical approach supported by comparative analysis of several jurisdictions, this research evaluates how existing legal frameworks regulate capital adequacy, asset segregation, insolvency mechanisms, transparency, and systemic risk in gold-related transactions. The analysis reveals the presence of regulatory fragmentation, potential overlap of supervisory authorities, and legal uncertainty regarding the proprietary status of gold claims, particularly within unallocated gold account structures. Such conditions may create opportunities for regulatory arbitrage while simultaneously increasing risks to financial system stability. The findings of this research indicate that a functional and activity-based regulatory model offers a more coherent approach to addressing the hybrid nature of bullion banking. Therefore, clearer legal classification of bullion-related products, harmonization of prudential and derivatives standards, and stronger cross-sector coordination among supervisory authorities are required in order to establish a more integrated legal framework, safeguard market integrity, and accommodate financial innovation in precious metals markets.